Elevated hypertriglyceridemia and decreased gallstones in the etiological composition ratio of acute pancreatitis as affected by seasons and festivals: A two-center real-world study from China - He, Wenhua; Wang, Gang; Yu, Bingjun; Xia, Liang; Zhu, Yong; Liu, Pi; Chen, Hua; Kong, Rui; Zhu, Yin; Sun, Bei; Lu, Nonghua (Frontiers in Cellular and Infection Microbiology, 2022)
Objective The purpose of this study was to observe the annual variation in the etiology of acute pancreatitis (AP) and its relationship with seasons and festivals. Methods From 2011 to 2017, 5146 adult patients with AP were studied, including 4110 patients from the First Affiliated Hospital of Nanchang University (South center) and 1036 patients from the First Affiliated Hospital of Harbin Medical University (North center). We analyzed the overall annual variation in the etiology of AP and then compared the differences in etiology between the two regions, as well as the effects of seasons and festivals on the etiology of AP. Results Gallstones, hypertriglyceridemia (HTG) and alcohol were the top three etiologies of AP. Gallstone AP showed a downward trend (P<0.001), and HTG-AP and alcohol AP showed an upward trend (both P<0.01). Among the etiologies of AP, gallstones and HTG were affected by seasons and festivals. The composition ratio of HTG-AP increased, while gallstone AP decreased in winter and in months with long holidays (all P<0.01). The composition ratio of gallstone AP in the south center was higher than that in the north center (59.5% vs. 49%), especially in summer (62.9% vs. 44.0%) and autumn (61.5% vs. 45.7%, all P<0.001). Conclusions The composition ratio of HTG-AP increased while gallstone AP decreased in the past 7 years, and they were affected by seasons and festivals.